The Advancement of The Accounting Profession in Nigeria After 2024 in Relation to Information and Communication Technology - Taiwo Hassan, Sulaiman; Deborah Ojochenemi, Egwuma (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2024)
Information and communication technologies' (ICTs') explosive growth will raise questions efficiently support the accounting industry in order to simplify the delivery of its goods and services in Nigeria beyond 2024. The role of ICT on the growth of the accounting profession in Nigeria was the main focus of this study. Using a tool called the role of ICT in Accounting Questionnaire (RIAQ), 60 accountants' opinions were purposefully gathered from the teaching and bursary staff of Nasarawa State University, Keffi, as well as the six banks that operate in Keffi Metropolis, in order to implement the survey study design. The chi-square statistic was employed in the data analysis to determine the degree to which ICT has helped the accounting industry, and the association between ICT and job competency in the accounting industry was examined using regression analysis. In summary, the study discovered a substantial correlation (P<0.05) between accounting proficiency and ICT use. According to the study's findings, ICT is crucial to Nigeria's accounting and Vision 2024 progress and achievement. It was suggested that accounting professionals should receive ongoing training in order to embrace and use ICT into accounting practice.